(untitled) (Proceedings of International Educators Conference, 2024)
After the process of separating the cotton fiber from the seed, various models of structures for extracting fiber from the saw teeth were theoretically analyzed, the proposed device for extracting fiber from the saw teeth was tested, and a new design was developed based on the results. A new design is simulated after determining the factors that increase the efficiency of fiber extraction.